2014
DOI: 10.3892/ijmm.2014.1666
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of apigenin against oxidative stress-induced damage in osteoblastic cells

Abstract: Apigenin, a plant-derived flavonoid, was investigated to determine whether it could influence hydrogen peroxide (H2O2)-induced oxidative damage and cellular dysfunction in the MC3T3-E1 mouse osteoblastic cell line. In the present study, osteoblastic cells were treated with H2O2 in the presence or absence of apigenin. Cell viability, apoptosis, reactive oxygen species (ROS) production and mitochondrial membrane potential (ΔΨm) were subsequently examined. It was observed that H2O2 reduced cell survival and ΔΨm, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
54
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(60 citation statements)
references
References 54 publications
5
54
0
1
Order By: Relevance
“…It prevents migration of neutrophils toward the inflammatory site; it inhibits platelet aggregation, hindering the cyclooxygenase (COX) pathway; it also inhibits production of proinflammatory cytokines (IL-1 β , TNF- α , IL-6, and IL-8) through inhibition of the activation of factor NF- κ B [123125]. …”
Section: Pathophysiology Of Peyronie's' Disease (Figure 1)mentioning
confidence: 99%
“…It prevents migration of neutrophils toward the inflammatory site; it inhibits platelet aggregation, hindering the cyclooxygenase (COX) pathway; it also inhibits production of proinflammatory cytokines (IL-1 β , TNF- α , IL-6, and IL-8) through inhibition of the activation of factor NF- κ B [123125]. …”
Section: Pathophysiology Of Peyronie's' Disease (Figure 1)mentioning
confidence: 99%
“…The studies by Hougee et al and Choi showed that apigenin inhibited IL-1b-induced prostaglandin synthesis, tumor necrosis factor (TNF)-induced IL-6 and IL-8 production in human peripheral blood mononuclear cells (PBMC) and TNF-alpha-induced secretion of osteoclastogenic cytokines such as IL-6 in MC3T3-E1 cells [21,22]. In addition, apigenin also attenuated oxidative-induced cell damage and increased osteoblast differentiation genes such as alkaline phosphatase (ALP), collagen, osteopontin (OPN), osteoprotegerin (OPG), bone sialoprotein (BSP), osterix (OSX) and osteocalcin (OC), and bone morphogenetic proteins (BMPs) genes in osteoblastic cells [23]. Furthermore, apigenin inhibited osteoclastogenesis and prevents bone loss in ovariectomized mice [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Physiological level of ROS is essential for the maintenance of normal cellular function, while excessive production of ROS leads to mitochondrial damage and cell injury [23, 24]. Given that ROS is noxious products of cellular metabolism and mainly produced by the mitochondria, linking mitochondrial respiration with ROS effects on cellular function is logical.…”
Section: Introductionmentioning
confidence: 99%